Playback-centric visualizations of video usage using weighted interactions to guide where to watch in an educational context - Lee, Hyowon; Liu, Mingming; Scriney, Michael; Smeaton, Alan F. (Frontiers in Education, 2022)
The steady increase in use of online educational tools and services has led to a large amount of educational video materials available for students to watch. Finding the right video content is usually supported by the overarching learning management system and its user interface that organises various video items by course, categories and weeks, and makes them searchable. However, once a wanted video is found, students are often left without further guidance on what parts in that video they should focus on. In this article, a timeline visualisation to augment the conventional playback timeline is introduced which employs a novel weighting strategy in which the history of different video interactions generate scores based on the context of each playback. This includes whether the playback started after jumping forward or backward in the video, whether the playback was at faster or slower speed, and whether the playback window was in focus on the student's screen or was in the background. The resultant scores are plotted in second-by-second bins on the additional timeline, making it in effect a playback-centric usage graph nuanced by how each playback was executed. Students are informed by this visualisation on the playback by their peers and can selectively watch those portions which the contour of the usage visualisation suggests. The visualisation was implemented as a fully-fledged web application and deployed in an undergraduate course at a university for full semester. 131 students used the system throughout the semester watching 52 videos, guided by the visualisation to selectively watch. Playback log analysis revealed that the selectively watched portions in videos corresponded to the important portions of the videos as assessed by the instructor who created the videos. The characteristics of this method as a way of guiding the students in where to watch as well as a complementary tool for playback analysis are discussed. However an overall under-use of the video materials by students forced us to rethink the way video learning materials are provided in an exclusively online delivery. Further insights into the potential values of this visualisation and its underlying weighting strategy are discussed.